Tinjauan Hukum Islam terhadap Praktik Uang Kethip di Pasar Dhoplang Desa Pandan Slogohimo Wonogiri - Agis Veronika; Kadenun Kadenun; Wahyudi Wahyudi (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Buying and selling is exchanging assets for assets in a certain way or exchanging something that is desired in a commensurate way through certain ways that are useful. Buying and selling transactions are activities that are permissible in Islam based on the Koran, hadith, and the consensus of the Ulama. In transactions at the Dhoplang Market, buyers are required to exchange rupiah into coins made of wood, this money is called kethip money and the place to exchange it is in a place to exchange money or called a place where money is exchanged. The data sources for this research are primary data sources where the data is obtained from buying and selling parties in the market and secondary data sources, namely data sources obtained from notes and books and are already related to the problems the author is researching. The method used by the author to collect information and data is using observation, interviews and documentation, as well as data analysis techniques using deductive analysis. The conclusion that can be drawn from this Kethip money is money made of wood and the nominal value is the same as the rupiah currency used in everyday life. How to use it, the buyer exchanges rupiah for kethip money, that is, exchanges it first at the place where the money is collected, after which the buyer can spend whatever has been provided by the seller, namely food, drinks and handicrafts. Transaction practices at the Dhoplang Market have fulfilled the pillars and conditions and legal status in Islam may be used.